KESULITAN MEMBACA PERMULAAN SISWA KELAS I SD NEGERI 010 BUKIT KAUMAN KABUPATEN KUANTAN SINGINGI - Elsa; Febrina Dafit (STKIP Subang, 2024)
This research aims to determine students' initial reading difficulties, and overcome the initial reading difficulties of grade 1 students at SDN 010 Bukit Kauman, Kuantan Singingi Regency. This type of research is research that uses a qualitative research method research approach based on the philosophy of postpositivism. The instruments of this research are tests, observation sheets, interview sheets, and documentation review sheets. Data were analyzed based on Miles and Huberman's theory with a sequence of steps for data reduction, data presentation, and drawing conclusions/verification. The results obtained from this research are: The results obtained from this research are the challenges of students' initial reading, the factors causing students' initial reading difficulties and teacher strategies to help students overcome students' initial reading in class 1 of SD Negeri 010 Bukit Kauman, Kuantan Singingi Regency. Students' initial reading challenges include; difficulty identifying letters, difficulty spelling words with diphthongs, consonants and affixes, stuttering and mispronouncing words. Factors causing initial reading difficulties are intellectual, contextual and psychological factors. The strategies for overcoming students' initial reading challenges are the use of learning materials, motivational counseling and individual reading sessions.